Childhood experience of father's job loss and stock market participation - Antti Lehtoranta (Bank of Finland, 2014)
Using data from the Panel Study of Income Dynamics (PSID), I document that childhood experience of father's job loss decreases the propensity to own stocks as an adult. If this experience takes place at the age of 5–10 years, the probability of owning stocks decreases by 2.9 percentage points in a sample with mean stock market participation rate of 17%. This finding is robust to alternative definitions of age ranges and controlling for random unobserved effects. I also find an effect of similar magnitude in the Health and Retirement Study (HRS) data.
URN:NBN:fi:bof-201412193440
Keywords: D03; D14; D83; G11; J64; 330; stock market participation; personal experience; job loss